Repression of Retrotransposal Elements in Mouse Embryonic Stem Cells Is Primarily Mediated by a DNA Methylation-independent Mechanism - Hutnick, Leah K. (American Society for Biochemistry and Molecular Biology, 2010)
In defense of deleterious retrotransposition of intracisternal A particle (IAP) elements, IAP loci are heavily methylated and silenced in mouse somatic cells. To determine whether IAP is also repressed in pluripotent stem cells by DNA methylation, we examined IAP expression in demethylated mouse embryonic stem cells (mESCs) and epiblast-derived stem cells. Surprisingly, in demethylated ESC cultures carrying mutations of DNA methyltransferase I (Dnmt1), no IAP transcripts and proteins are detectable in undifferentiated Oct4(+) ESCs. In contrast, ∼3.6% of IAP-positive cells are detected in Oct4(−) Dnmt1(−/−) cells, suggesting that the previously observed increase in IAP transcripts in the population of Dnmt1(−/−) ESCs could be accounted for by this subset of Oct4(−) Dnmt1(−/−) ESCs undergoing spontaneous differentiation. Consistent with this possibility, a dramatic increase of IAP mRNA (>100-fold) and protein expression was observed in Dnmt1(−/−) ESC cultures upon induction of differentiation through the withdrawal of leukemia-inhibitory factor for 6 or more days. Interestingly, both mRNAs and proteins of IAP can be readily detected in demethylated Oct4(+) epiblast-derived stem cells as well as differentiated mouse embryo fibroblasts, neurons, and glia upon conditional Dnmt1 gene deletion. These data suggest that mESCs are a unique stem cell type possessing a DNA methylation-independent IAP repression mechanism. This methylation-independent mechanism does not involve Dicer-mediated action of microRNAs or RNA interference because IAP expression remains repressed in Dnmt1(−/−); Dicer(−/−) double mutant ESCs. We suggest that mESCs possess a unique DNA methylation-independent mechanism to silence retrotransposons to safeguard genome stability while undergoing rapid cell proliferation for self-renewal.